The interaction of a thiosemicarbazone derived from R - (+) - limonene with lipid membranes. (January 2021) - Marquezin, C.A.; de Oliveira, C.M.A.; Vandresen, F.; Duarte, E.L.; Lamy, M.T.; Vequi-Suplicy, C.C.
Graphical abstract: Highlights: The new thiosemicarbazone 2-TSC affects the packing of DMPC bilayer decreasing the cooperativity of the gel-fluid transition. 2-TSC was found to act as a quencher of Laurdan fluorescence. ESR of a spin probe at the membrane core indicates that 2-TSC fluidizes the bilayer gel phase and rigidifies the fluid phase. Abstract: As a potential drug, 2-nitrobenzaldehyde-thiosemicarbazone (2-TSC), a thiosemicarbazone derived from the terpene R-(+)-limonene, was studied through calorimetric and spectroscopic techniques. Differential Scanning Calorimetry (DSC) data showed that 2-TSC causes structural changes in a 1, 2-dipalmitoyl- sn -glycero-3-phosphocholine (DMPC) membrane, strongly decreasing the cooperativity of the bilayer gel-fluid thermal transition. Optical absorption spectroscopy showed that 2-TSC is more soluble in ethanol and lipids than in water medium, and that the drug displays different structures in the different environments. Though 2-TSC displays no fluorescence, time resolved fluorescence showed that the drug is an effective quencher of the fluorescent probe 6-dodecanoyl-2-dimethylaminonaphthalene (Laurdan). As it is well accepted that Laurdan is positioned into the bilayer close to the membrane surface, that is possibly the localization of 2-TSC in a bilayer. Electron spin resonance (ESR) of the probe 1-palmitoyl-2-stearoyl-(14-doxyl)-sn-glycero-3-phosphocholine (14-PCSL) revealed that 2-TSC is inserted into the hydrocarbon part of the bilayer, fluidizing the lipid bilayer gel phase and rigidifying or organizing the bilayer fluid phase. Similar effects are found for other lipophilic molecules, including cholesterol. These results are useful to improve the understanding of the processes that govern the interaction of thiosemicarbazones with cell membranes, related to the activity of the drugs and their cytotoxicity.